Automated DNA fragments recognition and sizing through AFM image processing. - Ficarra, E.
This paper presents an automated algorithm to determine DNA fragment size from atomic force microscope images and to extract the molecular profiles. The sizing of DNA fragments is a widely used procedure for investigating the physical properties of individual or protein-bound DNA molecules. Several atomic force microscope (AFM) real and computer-generated images were tested for different pixel and fragment sizes and for different background noises. The automated approach minimizes processing time with respect to manual and semi-automated DNA sizing. Moreover, the DNA molecule profile recognition can be used to perform further structural analysis. For computer-generated images, the root mean square error incurred by the automated algorithm in the length estimation is 0.6% for a 7.8 nm image pixel size and 0.34% for a 3.9 nm image pixel size. For AFM real images we obtain a distribution of lengths with a standard deviation of 2.3% of mean and a measured average length very close to the real one, with an error around 0.33%.
Keywords: AFM image processing; DNA fragment size; DNA secondary structure transition; Atomic force microscope images; Automated DNA fragments recognition; Automated algorithm; Background noise; Computer-generated images; Image pixel size; Length estimation; Manual DNA sizing; Molecular profile; Molecular profile extraction; Physical properties; Processing time; Protein-bound DNA molecule; Root mean square error; Semiautomated DNA sizing; Structural analysis